(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
تهتم الرؤية الدرجية بدراسة المضلعات المتعامدة، ومن أهم المواضيع التي دُرست هو تعيين نواة المجموعة النجمية درجياً، فقد توصل الباحث تورانزوس إلى نتيجة هامة جداً في تعيين نواة المجموعة النجمية في حالة الرؤية العادية. ثم أثبتت الباحثة مارلين برين صحة نظريّة مرادفة لهذه النتيجة في حالة الرؤية الدرجية، كما تمكنت من إيجاد طريقة لتعين نواة المضلع المتعامد النجمي درجياً عندما يكون المضلع المتعامد بسيط الترابط. يهدف البحث إلى تعميم الطريقة السابقة عندما يكون المضلع المتعامد ثنائي الترابط والمركبة المحدودة للمتممة مستطيلاً حيث سنثبت صحة النتيجة الآتية: لتكن ، مضلعاً متعامداً مغلقاً ثنائي الترابط، حيث إنّ المجموعة نجمية درجياً، عندئذ إذا كانت جبهة المركبة المحدودة B للمجموعة مستطيلاً فإن نواة تتألف من مركبة أو مركبتين أو أربع مركبات. The staircase visibility concerns with the study of orthogonal polygon, one of the most important subjects which are studied is the Specification kernel of the orthogonal starshaped set. Toranzos represent a very important result in Specifying the kernel of the starshaped set in the usual notion of visibility via segments, after that Breen presented an analogue to this result of the staircase visibility. She also could find a way for Specifying the kernel of starshaped orthogonal polygon when this orthogonal polygon is a simply connected. The aim of this paper is generalizing the previous way when the orthogonal polygon is secondly connected and the bounded component for the complement is a rectangular; we will prove the following result: Let , be secondly connected closed orthogonal polygon, and staircase starshaped set. If the boundary of the bounded component for the complement is a rectangle ,so the kernel of is either one component or two or four ones.